Relative tax in a vertically differentiated market: The key role of consumers in environment - Giulia Ceccantoni; Ornella Tarola; Cecilia Vergari (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2017)
In this paper, under the assumption that green consumption has (at least partially) a social/psychological dimension, we analyse the effect of a carbon tax when it is imposed on consumers buying dirty products rather than on polluting firms. The amount of the tax paid is determined by the share of brown consumers in the market and the quality gap between variants. We show that this tax can abate emissions without inducing the undesirable relocation effect which can be observed in the case when a unilateral climate policy is imposed on polluting producers.
Keywords: H30; D43; Q5; L13; 330; Environmental quality; Vertical differentiation; Duopoly taxation; Consumer behaviour